Bridging Education Gap through Educational Innovation for Sustainable Development: A Bibliometric Analysis of the Scopus Database - Fatmawati, Novita Sari Dwi; Wulandari, Wida; Irawan, Nico (Universitas Muhammadiyah Surakarta, 2026)
This study examines the global research landscape on educational inequality and its contribution to achieving Sustainable Development Goal 4 (Quality Education) through a comprehensive bibliometric analysis. Using data retrieved from the Scopus database, 190 peer-reviewed journal articles and conference proceedings published between 2015 and 2025 were systematically analyzed. The bibliometric procedures included publication trend analysis, citation analysis, co-authorship networks, keyword co-occurrence, and thematic mapping using VOSviewer and Bibliometric software. The results indicate that research on the education gap has shown a stable but intensifying trend, with a significant increase in publications during and after the COVID-19 pandemic, reflecting growing global concern over widening educational disparities. The findings reveal that the education gap is primarily driven by socioeconomic status, digital inequality, family background, regional disparities, and teacher quality. Highly cited studies emphasize that inequalities in learning opportunities emerge from early childhood and are reinforced by unequal access to technology, quality schooling, and supportive learning environments. The analysis also identifies the United States, China, and the United Kingdom as the most influential contributors to this field, with strong international research collaboration patterns. Thematic and conceptual structure analyses demonstrate that educational inequality is closely linked to sustainable development, digital transformation, academic performance, and social inclusion. Importantly, this study highlights the growing relevance of policy-oriented solutions, including student loan systems, digital infrastructure development, and targeted social interventions, as strategic mechanisms to reduce educational inequality and expand access to higher education. Overall, this bibliometric mapping provides a comprehensive overview of the evolution, structure, and key drivers of research on the education gap. The findings offer valuable insights for policymakers, educators, and researchers in designing evidence-based strategies to promote equitable, inclusive, and sustainable education systems in support of SDG 4.